Serum CYR61 Is Associated With Airway Inflammation and Is a Potential Biomarker for Severity in Chronic Obstructive Pulmonary Disease - Tan, Zhu-Xia; Fu, Lin; Wang, Wen-Jing; Zhan, Ping; Zhao, Hui; Wang, Hua; Xu, De-Xiang (Frontiers in Medicine, 2021)
Background: Cysteine-rich 61 (CYR61) and inflammation was upregulated in the lungs of patients with chronic obstructive pulmonary disease (COPD). However, the association between CYR61 and inflammation was unclear in COPD patients. This study aimed to analyze the association of serum CYR61 with pulmonary inflammation and lung function indexes in COPD patients. Methods: One hundred and fifty COPD patients and 150 control subjects were enrolled. Serum and pulmonary CYR61 was detected. Lung function indexes were evaluated in COPD patients. Results: Serum CYR61 level was elevated and pulmonary CYR61 expression was upregulated in COPD patients. An increased CYR61 was associated with decreased pulmonary function indexes in COPD patients. Further analyses showed that nuclear factor-kappa B (NF-κB) p65-positive nuclei was elevated in the lungs of COPD patients with high level of CYR61. Accordingly, serum monocyte chemotactic protein (MCP)-1 and tumor necrosis factor α (TNF-α), two downstream inflammatory cytokines of NF-κB pathway, were increased in parallel with CYR61, among which serum MCP-1 and TNF-α were the highest in COPD patients with high level of CYR61. Moreover, a positive correlation, determined by multivariate regression that excluded the influence of age, gender and smoking, was observed between serum CYR61 and inflammatory cytokines in COPD patients. Conclusion: These results provide evidence that an increased CYR61 is associated with pulmonary inflammation and COPD progression. Inflammatory cytokines may be the mediators between CYR61 elevation and COPD progression.